Phytochemical investigations of Campsis radicans L. - Islam, Mirazul; Kuddus, Md Ruhul; Rashid, Mohammad Abdur; Haque, Mohammad Rashedul (Creative Pharma Assent, 2020)
Petroleum ether, dichloromethane and ethyl acetate soluble fractions were obtained through partitioning the crude methanolic extract of the leaves of Campsis radicans L. (Family. Bignoniaceae) followed by the chromatographic separation of secondary metabolites from them. A total of five triterpene compounds i.e., corosolic acid methyl ester (1), β-amyrin (2), arjunolic acid (3), maslinic acid (4) and 28-O-[β-D-glucopyranosyl-(1→6)-β-D-glucopyranosyl]-2α,3α,19α-trihydroxy-12-en-28-ursolic acid (5) were isolated from the dichloromethane fractions and their structures were characterized by 1H NMR spectroscopy and compared the NMR data with published values.